2020
DOI: 10.1080/02673037.2020.1803803
|View full text |Cite
|
Sign up to set email alerts
|

Tenure type mixing and segregation

Abstract: We examine the 'overlap' or to which degree tenure form patterns are similar to socio-economic segregation patterns. The issue has been discussed concerning mixing policies; does mixing of tenure hinder socio-economic segregation? If mixing tenure is to be an effective policy against segregation, the overlap has to be understood. Using Swedish register data, we cross tenure-type landscapes with patterns of high/mixed/low-income and with European/non-European/Swedish-born. To what degree is there overlap among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…The ability to enter home ownership is not only age-related and associated with access to parental support but has distinct spatial patterns (Coulter, 2018;Arundel and Ronald, 2021). A recent study by Andersson et al (2022) using extensive Swedish data found, for example, a strong degree of spatial overlap in tenure mix and socioeconomic mix across neighbourhoods. This paper brings socioeconomic mix and age segregation debates into conversation in a context of ageing and increasing housing precarity, particularly for younger people (Marcuse and Keating, 2006); it examines how lifecourse related housing market dynamics are shaping residential sorting.…”
Section: Age Segregation -A Results Of Housing Processes?mentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to enter home ownership is not only age-related and associated with access to parental support but has distinct spatial patterns (Coulter, 2018;Arundel and Ronald, 2021). A recent study by Andersson et al (2022) using extensive Swedish data found, for example, a strong degree of spatial overlap in tenure mix and socioeconomic mix across neighbourhoods. This paper brings socioeconomic mix and age segregation debates into conversation in a context of ageing and increasing housing precarity, particularly for younger people (Marcuse and Keating, 2006); it examines how lifecourse related housing market dynamics are shaping residential sorting.…”
Section: Age Segregation -A Results Of Housing Processes?mentioning
confidence: 99%
“…The ability to enter home ownership is not only age-related and associated with access to parental support but has distinct spatial patterns (Arundel and Ronald, 2021; Coulter, 2018). A recent study by Andersson et al (2022) using extensive Swedish data found, for example, a strong degree of spatial overlap in tenure mix and socio-economic mix across neighbourhoods.…”
Section: Introductionmentioning
confidence: 97%
“…The income gradient is strongest for Swedish‐born individuals with a non‐Swedish background (individuals born in Sweden with one or two immigrant parents) and for foreign‐born individuals, but less strong for Swedish‐born individuals with a Swedish background. Outside dense settlements, there is essentially no income gradient for Swedish born individuals irrespective of them having a Swedish or non‐Swedish background, see also (Andersson, Wimark, and Malmberg 2020). But for foreign‐born individuals, there are signs of an income gradient, even though the pattern is rather diffuse.…”
Section: Ethnic Segregation and Income Sortingmentioning
confidence: 99%
“…The flow on effects of socio-spatial segregation veer towards the designation of vulnerable neighbourhoods and evince claims that privilege in urban landscapes is 'simultaneously historical and spatial' (Pudilo 2000: 16), they are also maintained discursively through media rhetoric and political governance too (Norquay & Drozdzewski, 2017;Östh et al, 2018;Svallfors, 2004). Indeed, a sizeable quantity of scholarship on the neighbourhood effects of Swedish neighbourhoods has focused on socio-spatial segregation, and the outcomes of specific histories of housing tenure and development in place (Abramsson & Andersson, 2015;Andersson et al, 2020;Malmberg et al, 2013Malmberg et al, , 2018Strömblad & Malmberg, 2016;Wimark et al, 2019Wimark et al, , 2020. With pressure on housing in Swedish neighbourhoods unlikely to abate soon, and recurring media and political focus on 'vulnerable' neighbourhoods, we argue that lateral and diversified approaches to (re)visiting (Swedish) neighbourhoods from experiential, embodied and emplace perspectives -including those that extend neighbourhood effects research through qualitative approaches -is paramount and pressing.…”
Section: Writing From (Our) Neighbourhoods: Contexts and Positionsmentioning
confidence: 99%